Degeneration of salivary glands of males of the tick Rhipicephalus sanguineus (Latreille, 1806) (Acari, Ixodidae) - Scopinho Furquim, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Elsevier B.V., 2008)
The present study examined the salivary glands of Rhipicephalus sanguineus males at days 0, 3, and 7 post-detachment from the host. Degeneration of this organ occurred in the three stages and it advanced as time away from the host progressed. Thus, characteristics of degeneration were more prominent in males at day 7 post-detachment than in males at day 0 post-detachment. In males at day 0 post-detachment, type I acini were intact; while in other stages these acini exhibited signs of degeneration. In type 11 acini of individuals at day 0 post-detachment, cells a, c1-c5, c8, and indeterminate were identified. Only c I and c8 were intact. The remaining cell types were undergoing degeneration, as well as all cells d-f in type III acini, and all g in type IV acini.In males at day 3 post-detachment from the host, all cells (a, c1-c5, c8 and indeterminate) of type 11 acini, cells d and e in type III acini, and g in type IV were undergoing degeneration. In some Indeterminate acini, the boundaries of cells still could be distinguished, while in others, only a cytoplasmic mass was observed. At day 3 post-detachment, apoptotic bodies were present.In males at day 7 post-detachment from the host, the degeneration process progressed. All cells a, cl, c3-c5, c8 and indeterminate in type II, and d and e in type III acini were undergoing degeneration. Type IV acini still contained remnants of secretion and in Indeterminate acini, only a cytoplasmic mass could be observed. At this stage, apoptotic bodies were also present.The present study still revealed that cells of salivary glands of R. sanguineus males when degenerating undergo the following changes: (a) decrease in secretion production with or without granule breakage, (b) changes in nuclear morphology, (c) cytoplasm shrinkage, (d) loss of cell shape, (e) loss of cell boundaries, and (e) cytoplasmic vacuolation. Together, these changes result in cell fragmentation with release of apoptotic bodies. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus sanguineus; Salivary gland; Tick; degeneration; feeding stage; Morphology